2018
DOI: 10.1007/s10714-018-2467-0
|View full text |Cite
|
Sign up to set email alerts
|

Are there any models with homogeneous energy density?

Abstract: By applying a recent method -based on a tetrad formalism in General Relativity and the orthogonal splitting of the Riemann tensor-to the simple spherical static case, we found that the only static solution with homogeneous energy density is the Schwarzschild solution and that there are no spherically symmetric dynamic solutions consistent with the homogeneous energy density assumption. Finally, a circular equivalence is shown among the most frequent conditions considered in the spherical symmetric case: homoge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The uniform density spherical matter configuration is the standard entry point in all textbooks of General Relativity and Relativistic Astrophysics [34,35,36,37]. We have recently shown [2] that, despite its simplicity and pedagogical interest, this widespread assumption is very restricted. Any dynamic homogeneous density profile satisfying the Karmarkar condition will lead to the Schwarzschild solution.…”
Section: The Static Casementioning
confidence: 99%
See 2 more Smart Citations
“…The uniform density spherical matter configuration is the standard entry point in all textbooks of General Relativity and Relativistic Astrophysics [34,35,36,37]. We have recently shown [2] that, despite its simplicity and pedagogical interest, this widespread assumption is very restricted. Any dynamic homogeneous density profile satisfying the Karmarkar condition will lead to the Schwarzschild solution.…”
Section: The Static Casementioning
confidence: 99%
“…Most of them are recent and devoted to describing compact objects with anisotropic equations of state. On the right plate, the publications are grouped, attending to the commonly cited references in each paper case, showing that it is possible to obtain relevant information from self-gravitating systems [1,2]. This formalism provides coordinate-free results expressed in terms of structure scalars closely related to the kinematical and physical properties of the fluid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This formalism provides coordinate-free results expressed in terms of structure scalars related to the kinematical and physical properties of the fluid. We showed that it is possible to obtain relevant information for self-gravitating systems in a simple form from these scalars [14,15]. Based on the formalism above, we provide a method to integrate all possible orbits for any stationary axially symmetric solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Chan studied numerically its solutions in separated variables [20][21][22][23]. The questions of cavity evolution and constant energy density were discussed in [24,25]. Other authors realized that the main junction condition is a Riccati equation in time for the metric component g rr [26][27][28].…”
Section: Introductionmentioning
confidence: 99%